FAKTOR RISIKO DIABETES MELITUS TIPE 2 PADA JEMAAH HAJI DAERAH ISTIMEWA YOGYAKARTA :Analisis Data Siskohatkes Tahun 2023 - Lintang Tyas Pramesti (2024)
Type 2 diabetes mellitus is a dangerous risk factor for cardiovascular disease for Hajj pilgrims, especially the elderly age group. The prevalence of this disease has increased by 2% from 2013 to 2018. This research was conducted to determine the risk factors for the occurrence of diabetes mellitus among Hajj pilgrims in the Special Region of Yogyakarta. The data used came from the Integrated Hajj Health Computerized System (Siskohatkes) 2023 with a cross-sectional study design. The analysis included univariate, bivariate (chi-square test), and multivariate (cox regression test). The results of the multivariate analysis showed that age ≥ 45 years (aPR=3,05; 95%CI 1,92-4,85), family history of DM (aPR=1,94; 95%CI 1,56-2,42), obesity (aPR=1,42; 95%CI 1,11-1,82), hypertension (aPR=1,42; 95%CI 1,19-1,70), and gender (aPR=0,73; 95%CI 0,61-0,88) have a significant relationship with age being the most dominant variable associated with the occurrence of type 2 DM among Hajj pilgrims in the Special Region of Yogyakarta. In this study, no significant relationships were found for variables such as education level, occupational status, HDL, and LDL. The researcher recommends that Hajj pilgrims undergo screening and early detection for type 2 DM, especially for those aged ≥ 45 years.